2015
DOI: 10.5901/mjss.2015.v6n4s3p360
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and Women Micro-Enterprise Performance: A Conceptual Framework

Abstract: This study aims at examining the impact of social networks on women micro-enterprise's performance in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
0
17
0
5
Order By: Relevance
“…Spring (2009), in her study of women's entrepreneurship and SC in Africa, argued that women with a lower socioeconomic status relied heavily on strong ties, whereas those at the higher end of the socioeconomic ladder had and could use weak ties. Ekpe et al (2015, p. 362) noted that women with high‐growth resources tended to use more formal networks, whereas those with low growth resources tended to employ informal social networks. In patriarchal Islamic societies, where familial and religious norms dictate the rules of networking, women face additional barriers to the development of their entrepreneurial SC, which is one of the key elements of their business success (Roomi, 2013).…”
Section: Developing An Sc Theoretical Frame For Women's Entrepreneurshipmentioning
confidence: 99%
“…Spring (2009), in her study of women's entrepreneurship and SC in Africa, argued that women with a lower socioeconomic status relied heavily on strong ties, whereas those at the higher end of the socioeconomic ladder had and could use weak ties. Ekpe et al (2015, p. 362) noted that women with high‐growth resources tended to use more formal networks, whereas those with low growth resources tended to employ informal social networks. In patriarchal Islamic societies, where familial and religious norms dictate the rules of networking, women face additional barriers to the development of their entrepreneurial SC, which is one of the key elements of their business success (Roomi, 2013).…”
Section: Developing An Sc Theoretical Frame For Women's Entrepreneurshipmentioning
confidence: 99%
“…Al margen de la heterogeneidad de definiciones (Tunal, 2003) sobre las diversas categorías empresariales (micro, pequeñas o medianas empresas), muchos autores coinciden en la importancia que tienen estas unidades productivas (Abor & Quartey,32 2010; Cabra, 2013;Harash, Al-timimi, & Alsaadi, 2014;OIT, 2005). Incluso los gobiernos han realizado programas para fomentar las iniciativas empresariales, a fin de incrementar las oportunidades de las poblaciones con menos recursos (Afande, 2015;Ekpe, Mat, & Ekpe, 2015;Kahsu, 2015;Ministerio de Economía Planificación y Desarrollo de la República Dominicana, 2010;OIT, 2013b). Este reconocimiento ha conllevado la necesidad de estudiar los factores que pueden explicar el fracaso o el éxito de las empresas, pues iniciar una empresa implica la posibilidad de tener éxito o fracasar (Mwobobia, 2012).…”
Section: íNdiceunclassified
“…A pesar de esto, muchas microempresas no llevan ningún tipo de registros contables de sus operaciones (Ekpe et al, 2015;Londoño & Mataix, 2012;Marulanda & Otero, 2005) y muchas veces aquellas que registran sus operaciones lo hacen con el propósito de minimizar los impuestos más que como fuente de información estratégica (García & Duréndez, 2007;Mbogo, 2011). El conocimiento empírico que puede tener un propietario de microempresa no sustituye la utilidad de la información contable como diagnóstico efectivo de la operación financiera de la empresa (Rangel et al, 2015).…”
Section: Tenencia De Sistema Contable En La Empresaunclassified
See 1 more Smart Citation
“…EO at an individual farmer level. In an agricultural context,(George, Reddi, Priti, Tufool, & S., 2015) defined and measured entrepreneurial intentions as the willingness to engage in new business activities, ventures, or projects within the following three years.. Several studies in multiple contexts of emerging economies found a strong positive relationship between the aforementioned dimensions of EO and entrepreneurial intentions(Ekpe, Mat, & Ekpe, 2015;Koe, 2016;. This suggests the possibility that, in the context of farms in emerging economies entrepreneurial intentions in individuals may be considered as a dimension effectively reflecting EO along with innovativeness, risk-taking, and proactiveness.Within the agricultural context, the relationships between farmers' EO and their innovation have hardly been explored yet, leaving a knowledge gap on how psychological antecedents affect farmer innovation.…”
mentioning
confidence: 99%